Good Charts The HBR Guide to Making Smarter, More Persuasive Data Visualizations. - Berinato, Scott (La Vergne : Harvard Business Review Press, 2023)
"The best, most powerful way to communicate the nature and potential impact of data is visually. For a long time "dataviz" was left to specialists-data scientists and professional designers. No longer. A new generation of tools and massive amounts of available data make it easy for anyone to create visualizations that communicate ideas far more effectively than generic spreadsheet charts ever could. The companies that invest in improving their visual communication will gain a competitive advantage, seeing threats and finding opportunities others don't. For individuals like you, building good charts is a need-to-have skill. If you're not doing it, other managers are, and they're getting noticed for it and getting credit for contributing to your company's success. In this updated and expanded edition of Good Charts, dataviz maven Scott Berinato provides the essential guide to how visualization works and how to use this new language to impress and persuade. Berinato lays out a system for thinking visually and building better charts through a process of talking, sketching, and prototyping. From tips and tricks for upping your visualization's clarity to laying out a system for storytelling with data, Good Charts covers all the core skills you need and can develop. This new edition includes added visuals and updates the landscape of visualization tools. It also includes new chapters on building dataviz teams and creating workflows to integrate visualization into everything you do. Good Charts is your go-to resource for turning plain, uninspiring charts and presentations that merely present information into smart, effective visualizations that powerfully convey ideas"--
A Brief History of Dataviz -- When a Chart Hits our Eyes -- Two Questions, Four Types -- Better Charts in a Couple of Hours -- Refine to Impress and Persuade -- Facts and Truth -- Present to Impress and Persuade -- A Return to Teamwork.
Description based upon print version of record.
Added to collection customer.56279.3
Keywords: Business presentations -- Charts, diagrams, etc; Visual communication; Communication in management; Computer graphics